A Novel Method to Produce an Artificial Common Bile Duct Using Electrospinning Technique. (2015) - Moazeni, N.; Semnani, D.; Latifi, M.; Sadrjahani, M.
Abstract: Reconstruction of the extrahepatic bile duct is one of the most common challenges for hepatobiliary surgeons to repair bile duct injury or defect. In this research, a novel method to produce an artificial common bile duct using electrospinning technique was introduced and the effect of polymer concentration on the compliance of produced prostheses is investigated. In addition, the optimum conditions of polyurethane nanofibrous tubes to reach the compliance of native common bile duct are determined. The results show that the compliance of the samples increases gradually with an increase in polymer concentration. Therefore optimum artificial prosthesis which was manufactured under conditions of concentration 8% w/v, applied voltage 1.0 kV, feed rate 0.5 ml/h and a tip-to-collector distance 15 cm can be applied as bile duct tissue.